The Effect of Folic Acid and Nicotinic Acid on Malondialdehyde Levels of Semen in Oligospermia Men after Cryopreservation - Zahra Sadeghi; Shahla Ishaqi; Gholam Reza Reza Dashti (مجله دانشکده پزشکی اصفهان, 2021)
Background: Reactive oxygen species (ROS) are of the most important detrimental factors on sperm quality during freezing process, which increases the lipid peroxidation (LPO) of cell membranes. In this study, the concentration of malondialdehyde (MDA) levels in semen of men with oligospermia before and after cryopreservation process was measured to evaluate the effect of folic acid and nicotinic acid on the MDA concentration after freezing.